The Influence Of Profitability, Leverage, Capital Intensity, and Tax Haven On Tax Avoidance In Mining Companies Listed On The Indonesia Stock Exchange In 2019-2023 - Wijayanti, Fatimah; Wafiroh, Novi Lailiyul (Jurnal Akuntansi, 2025)
This research aims to analyze the effect of profitability, leverage, capital intensity, and tax haven on tax avoidance in mining companies listed on the IDX in 2019-2023. Documentation techniques are used in secondary data collection methods in the form of financial reports of companies listed on the IDX since 2019-2023. This study is quantitative using a purposive sampling method. The sample used was 13 companies. This study uses Eviews 12 software in conducting statistical analysis. The results of this study are that profitability has no significant effect on tax avoidance (H1); leverage has no significant effect on tax avoidance (H2); capital intensity has a significant effect on tax avoidance (H3); tax haven has no effect on tax avoidance (H4), and profitability, leverage, capital intensity, and tax haven do not simultaneously affect tax avoidance (H5).